You cannot conserve a species that has not been found: The case of the marine sponge Axinella polypoides in Liguria, Italy. Issue 4 (19th January 2021) - Azzola, Annalisa; Bavestrello, Giorgio; Bertolino, Marco; Bianchi, Carlo Nike; Bo, Marzia; Enrichetti, Francesco; Morri, Carla; Oprandi, Alice; Toma, Margherita; Montefalcone, Monica
Abstract: Detailed knowledge about the distribution of species in need of protection is required for the management of Marine Protected Areas, a major tool to reduce marine biodiversity loss. Such knowledge is deficient for most marine invertebrates. Axinella polypoides is a marine sponge included on the list of protected species by the Barcelona Convention (1976) and the Bern Convention (1987). This large and erect species has an important ecological role in habitat forming and benthic–pelagic coupling. Bathymetrical, geographical and ecological data over the last 60 years were collated from publications and reports, together with new surveys to assess the distribution and protection status in Liguria of A. polypoides . It identified a more widespread distribution than previously thought, which points at a general need for dedicated investigations on the occurrence of species that require protection. Bathymetrical distribution was trimodal, with peaks corresponding to different geomorphological settings: coastal cliff bases (around 38 m depth), inner shelf shoals (52 m) and rocks amidst coarse sediment on the outer shelf (79 m). Density was significantly greater at the shallowest depths. The species was mostly found in the coralligenous biocoenosis, in association with other characteristic species or forming a monospecific facies. On (sub)vertical cliffs, A. polypoides often exhibited an unusual cane shape, rather than the typical bushy morphology, thus causing confusion with the congeneric A. cannabina, a more southern species. Records of the latter in the Ligurian Sea therefore need confirmation. Only a minority (22.6%) of A. polypoides records were in Marine Protected Areas, the remainder being located in areas with no current environmental protection plans in place. While the occurrence of this species in MPAs remained stable over the decades, the only quantitative historical data available indicated that populations in non‐protected areas were declining owing to anthropogenic impacts (fishing and anchoring).